Internal communication as a mediator in the relationship between transformational leadership and academic staff’s readiness for change in higher education - Saharudin Saharudin; Ekawarna Ekawarna; Urip Sulistiyo; Mohd. Odha Meditamar; Santo Kristiyono (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to explore the specific factors influencing academic staff’s readiness for organizational change at Islamic State University (IAIN) Kerinci, Indonesia, focusing on the mediating role of internal communication. The study examines the direct and indirect effects of organizational change readiness, transformational leadership behavior, and internal communication on staff readiness to change. A sample of 118 academic staff (40 male and 78 female) participated in this empirical study. Data were collected using an online survey, employing a Likert scale to measure the constructs. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test the hypotheses, with the PLS Algorithm assessing the measurement model and PLS Bootstrapping testing the structural model for mediation effects. Results revealed that organizational change readiness, transformational leadership behavior, and internal communication each have a significant positive effect on staff readiness for change. Internal communication was found to mediate the relationship between transformational leadership and organizational change readiness on academic staff's readiness for change. Key statistical results include a significant p-value (p < 0.05) and strong mediation effects, further emphasizing the importance of effective internal communication in facilitating organizational change. The cross-sectional survey design introduces limitations, including potential response bias due to self-reporting.This study contributes to the literature on organizational change by highlighting the role of internal communication as a mediator and the unique context of Islamic higher education institutions.